The Duke of Lennox, 1574 1624: A Jacobean Courtier s Life. David Bergeron. Edinburgh: Edinburgh University Press, 2022. x + 244 pp. $110 - Kern, Darcy (Renaissance Quarterly, 2023)
Keywords: book.review; dept.his

Community and identity in Castilian histories of the fifteenth century - Kern, Darcy (Sharq al-Andalus, 2021)
La historia fue tan importante para la construcción de la identidad comunitaria y la legitimidad política en el siglo XV como lo es hoy, y en los reinos de España igualmente tenso. Los cronistas y biógrafos católicos castellanos parecen inseguros del estado preciso de los moros en Iberia. Todos estaban de acuerdo con el control político o el señorío de los cristianos castellanos, pero pocos tenían una idea clara de las implicaciones de ese señorío para los moros. ¿Debería permitirse a los moros permanecer como parte de la comunidad una vez que un monarca cristiano castellano tomara el control de su ciudad, región o reino, o no había posibilidad de que pertenecieran? Rodrigo Sánchez de Arévalo (1404-1470), Fernán Pérez de Guzmán (c. 1377-c. 1460), Alonso Fernández de Palencia (1423-1492), Hernando de Pulgar (1436-c. 1492), y Mosén Diego de Valera (1412-1488) dieron diferentes respuestas. Todos coincidieron en que la comunidad castellano-leonesa existía antes de al-Andalus y, por lo tanto, era la comunidad política legítima de Hispania. La mayoría de ellos aceptaron la presencia de Granada de facto pero no de jure. Sin embargo, Arévalo, Valera y Pulgar sugieren la posibilidad de una comunidad política musulmana de jure bajo dominio castellano; Palencia y Guzmán no.
Accepted: 2021-07-14T06:58:23Z
Keywords: dept.his

A Narrative That Was Not Her Own: Mary I as Mediterranean Queen - Kern, Darcy (Writing Mary I: History, Historiography, and Fiction, 2022)
Nearly every biography of Mary Tudor mentions her acquisition of the Kingdom of Naples and the Spanish kingdoms through her marriage to Philip Habsburg, later Philip II of Spain, but they say little about her role as queen consort, primarily because she failed to control the narrative of her reign. She made little effort to patronize writers, disperse her symbols, send images of herself, use masculine terminology like her grandmother Isabel of Castile, or involve herself in the governance of her Mediterranean kingdoms. Her real and symbolic absence in the south, and the presence of Doña Juana, Philip’s sister and the capable regent of the Spanish kingdoms in his absence, led to her marginalization. This has had long-lasting consequences for the historiography of her reign, as historians have generally confined themselves to studying her in her English context using the gendered language of early Spanish writers while omitting her entirely from Naples.
Keywords: award_winner; dept.his